유사장치의 건전성데이터 분석을 통한 수소충전소 기능안전 추론방안 - 오봉식; 박상철; 장중순 (신뢰성 응용연구, 2021)
Purpose: There has been a substantive expansion of FCEV in the hydrogen economy. According to the government’s policy, the installation and operation of HRSs (Hydrogen Refueling Station) are expected to be carried out rapidly. However, the types of failures among the major devices of HRS such as compressors, coolers, and dispensers, and technologies related to the safety and reliability of data are not well disclosed. In the case of foreign (Germany, France, etc.) products of HRS in Korea, it is not easy to access technology, and to reduce risks in operating HRS, it is necessary to solve the problem in this area. Methods: HRSs are required to have the highest level of safety and reliability, but due to certain terms and conditions among suppliers, the main characteristics of the technology are not openly available. Based on the analysis done, in this paper we suggest improvement plans to curb the problems mentioned above . Results: PHM(Prognostics and Health Management) through failure type analysis of similar devices and safety-based real-time risk severity rating of HRS through technology that collects, analyzes, and evaluates and judges functional safety real-time safety risk data based on operational data are extremely important. A monitoring technique was presented to collect results through the methods mentioned above. Conclusion: In order to secure safety for safety-based risk reduction for an HRS’s operation, site selection for an HRS that meets functional safety and construction requirements is needed. It is also important that the required technology selected for this purpose, presented by the HRS standard, be applied to design. In addition, post-maintenance technology that can sustain risk reduction is also required.
Keywords: HRS(Hydrogen Refueling Stations); Smart Sensor; Functional Safety; PHM(Prognostics and Health Management); SIL(Safety Integrity Level)